Peningkatan Ketahanan Pangan Keluarga melalui Edukasi dan Demonstrasi Kebun Pangan - Mardhotillah, Mardhotillah; Amanda, Rahel; Angelica, Aisyah; Faizan, Adilah Alya; Syafiqah, Nadiya Rifdah; Nabella, Lutfhiana; Nazara, Adventria Howu; Herlian, Mayang Morly; Chusna, Amilatul; Alfiyyah, Anisah; Agustina, Agustina; Fahrizal, Muhammad; Amalliyah, Puji (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Household food security is a critical pillar in achieving community self-sufficiency and well-being, especially in rural areas. This article discusses an educational and demonstration program on home food gardening implemented in Karang Sari Village, aimed at enhancing residents' knowledge and skills in utilizing their home yards for growing food crops. Objective: The purpose of this service was to increase household food security by educating and demonstrating gardening techniques to villagers, thereby empowering them to make better use of their home yards for food production. Method: This public service was conducted through educational sessions, pre- and post-tests, planting demonstrations, and distribution of seeds (corn, cucumber, bitter melon, and long bean) to 50 participants from five hamlets in Karang Sari Village. Result: Evaluation results showed an average increase in knowledge of 19.6%. The highest improvements were in understanding corn cultivation (48%), repeated fertilization needs (24%), and long bean harvesting periods (26%). The smallest increase (4%) was related to the benefits of home gardening in reducing household expenses, indicating participants already had strong baseline knowledge. Conclusion: The program effectively enhanced community food literacy and promoted household food security through an educational and hands-on approach. It demonstrated that targeted education and practical demonstrations can significantly improve household food security in rural settings.